2- and 3-Monochloropropanediols in paper products and their transfer to foods. Issue 9 (1st September 2016) - Becalski, Adam; Zhao, Tony; Breton, Francois; Kuhlmann, Jan
ABSTRACT: The occurrence of 2- and 3-monochloropropanediol (MCPDs) in selected paper products sold on the Canadian market and the transfer of 3-MCPD from those products to beverages was probed. Products included coffee filters, tea bags, disposable paper hot beverage cups and milk packaged in paperboard containers. The occurrence MCPDs in coffee and tea filters on the German market was investigated as well. Furthermore, the presence of MCPDs in paper towels on the German market was also investigated. Analytes were determined by stable isotope dilution analysis GC-MS in SIM mode. 3-MCPD was detected in most paper products with levels ranging from a few nanograms in tea bags to a few micrograms in white coffee filters. Milk containers' paperboard contained 3-MCPD at about 500–1500 ng g –1 ; however, 3-MCPD was detected in milk only in smaller containers, 237–500 ml (likely due to a lower volume/surface ratio) at levels of about 1 ng g –1 . Out of three disposable hot beverage paper cups tested (of 237–473 ml capacity), paperboard of two contained 3-MCPD at 632–792 ng g –1, and 3-MCPD was detected in leachate from those paper cups at levels of about 16 ng per cup. 3-MCPD was detected in all paper towels at levels of 42–2466 ng g –1 . 2-MCPD was detected in many paper products (from Canadian and German sources) and in all the towels tested at levels varying from about 0.5–10% of that of 3-MCPD.